FOSTERING ECONOMIC SELF-RELIANCE IN MEKAR BERSATU VILLAGE, CENTRAL LOMBOK, THROUGH THE STRENGTHENING OF MICRO, SMALL, ADAN MEDIUM ENTERPRISES (MSMES) - Chasanah, Afrida Nur; Supratman, Supratman; Krisnahadi, Tama; Septika, Baiq Herdina; Ilhamalimy, Ridho Rafqi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Mekar Bersatu Village possesses considerable economic potential, particularly in the agricultural and handicraft sectors that are based on local resources. However, local Micro, Small, and Medium Enterprises (MSMEs) face several persistent challenges, including limited market access, low adoption of digital technologies, and the lack of legal business status. This community engagement initiative aims to enhance the capacity of local MSMEs through targeted interventions focusing on digital marketing training and business legalization, aligned with the village’s unique local potential. The methodology involved a needs assessment survey, followed by two training sessions—on digital marketing and business legalization—along with practical simulation exercises. Evaluation outcomes indicate a significant increase in participants' understanding of digital marketing strategies and the importance of legal business registration. The program successfully motivated participants to utilize social media as a promotional platform and to independently initiate business licensing processes. These outcomes demonstrate that the training constitutes a foundational step toward fostering sustainable economic independence in Mekar Bersatu Village. ABSTRAKDesa Mekar Bersatu memiliki potensi ekonomi yang cukup besar, khususnya di sektor pertanian dan kerajinan tangan yang berbasis pada sumber daya lokal. Namun, Usaha Mikro, Kecil, dan Menengah (UMKM) setempat menghadapi beberapa tantangan yang terus berlanjut, termasuk akses pasar yang terbatas, rendahnya adopsi teknologi digital, dan kurangnya status bisnis yang sah. Inisiatif keterlibatan masyarakat ini bertujuan untuk meningkatkan kapasitas UMKM setempat melalui intervensi yang ditargetkan dengan fokus pada pelatihan pemasaran digital dan legalisasi bisnis, yang selaras dengan potensi lokal desa yang unik. Metodologi yang digunakan melibatkan survei penilaian kebutuhan, diikuti oleh dua sesi pelatihan—tentang pemasaran digital dan legalisasi bisnis—bersama dengan latihan simulasi praktis. Hasil evaluasi menunjukkan peningkatan yang signifikan dalam pemahaman peserta tentang strategi pemasaran digital dan pentingnya pendaftaran bisnis yang sah. Program ini berhasil memotivasi peserta untuk memanfaatkan media sosial sebagai platform promosi dan untuk secara mandiri memulai proses perizinan bisnis. Hasil ini menunjukkan bahwa pelatihan merupakan langkah mendasar menuju pembinaan kemandirian ekonomi yang berkelanjutan di Desa Mekar Bersatu.